Application of Immunotherapy in Hepatocellular Carcinoma - Miao, Lele; Zhang, Zhengchao; Ren, Zhijian; Li, Yumin (Frontiers in Oncology, 2021)
Hepatocellular carcinoma is one of the most common malignancies globally. It not only has a hidden onset but also progresses rapidly. Most HCC patients are already in the advanced stage of cancer when they are diagnosed, and have even lost the opportunity for surgical treatment. As an inflammation-related tumor, the immunosuppressive microenvironment of HCC can promote immune tolerance through a variety of mechanisms. Immunotherapy can activate tumor-specific immune responses, which brings a new hope for the treatment of HCC. At the present time, main immunotherapy strategies of HCC include immune checkpoint inhibitors, tumor vaccines, adoptive cell therapy, and so on. This article reviews the application and research progress of immune checkpoint inhibitors, tumor vaccines, and adoptive cell therapy in the treatment of HCC.